Characterization of volatile compounds and bioactive compounds of pulp and jelly of cagaita by solid phase microextraction in the headspace mode and mass spectrometry by paper spray (Research, Society and Development, 2021)
The cagaiteira (Eugenia dysenterica) belonging to the Myrtaceae family, is a tree native to the Brazilian Cerrado, its fruit is very fragile, with thin bark and juicy pulp, it is consumed in the processed form as a jelly to prolong its useful life. The present work had as objective to elaborate cagaita jelly and to evaluate the alteration of bioactive compounds and volatile compounds in relation to the pulp in natura. The analysis of mass spectrometry by paper spray in positive and negative modes allowed the identification of several substances, among them, organic acids, sugars, anthocyanins, hydroxycinnamic acids, hydroxybenzoic acids and flavonoids, indicating that the production of jelly can be a technique for conservation of phenolic compounds with their respective sensory qualities such as color and flavor. In the analysis of volatiles by solid phase microextraction in headspace mode, monoterpenes, hydrocarbons and sesquiterpenes were detected, indicating that the production of jelly can preserve the characteristic aroma of the fruit. In the characterization of volatile compounds in cagaita pulp, 3-carene was the major monoterpene found. While processing jelly there was production of furaldehyde, a product obtained as a natural consequence of heating.